Manifestasi Acturian Terhadap Tanggung Jawab Berkelanjutan Pada Anak Yatim Piatu Korban Pandemi Covid-19 - Pandoman, Agus (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2023)
This study aims to examine using a structural approach regarding the institutional scope of world bodies in manifesting Acturian Actors in the context of global children's rights as a strengthening of regulations on sustainable custody that must be applied by every member country of the United Nations in responding to the lives of orphans who are victims of the pandemic. covid-19. With a structural and qualitative approach, it can be concluded that the pattern of handling tends to use a pattern of disaster management which is feared to prolong the uncertainty of the substance of the ongoing responsibility for orphans who are victims of Covid 19.